Метрологическое обеспечение технологий GPON/GEPON - Холод, Л. Н. (ХНУРЕ, 2019)
The article deals with the issues of metrological support technology using Passive Optical Network – PON, in par-ticular technology GPON (Gigabit-capable Passive Optical Network) and GEPON (Gigabit Ethernet Passive Optical Network) during the implementation and operation of the network: input control of metrological parameters of linear cable products, terminal equipment and optical splitters for compliance with the quality of the products supplied with the declared passport values according to the requirements SLA (Service Level Agreement) QoS model. In addition, when carrying out installation and construction works for quality control of the carried-out works, identifying and elim-inating the cause of the degradation of the quality of transmitted signals. Metrological support of acceptance tests after the completion of installation and construction works to confirm network parameters ensuring the quality of transmitted information. Operational measurements taken during the operation of the network, which are aimed at ensuring the quality parameters of the transmitted information and the timely elimination of problems and damages to the network. For all stages, a set of measuring instruments has been defined, with the help of which the tasks are solved, considered the specificity of point-to-multipoint tree topology measurements in passive optical networks, identified problems aris-ing from the operation of networks GPON/GEPON and indicate the direction of their decision.
Keywords: GPON; GEPON; QoS; PON